2016
DOI: 10.3390/nu8060353
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Analyzing the Biological Effects of Resveratrol

Abstract: The suggested health effects (e.g., disease prevention) of dietary bioactive compounds such as resveratrol are challenging to prove in comparison to man-made drugs developed for therapeutic purposes. Dietary bioactive compounds have multiple cellular targets and therefore have a variety of biological effects. Extrapolating the biological effects of dietary compounds from in vitro and in vivo animal experiments to humans may lead to over- or under-estimation of the effect and role of these compounds. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 128 publications
(132 reference statements)
2
29
0
Order By: Relevance
“…The plasma resveratrol concentrations measured at after two and four weeks of resveratrol administration ranged from 0.7 to 2.55  μ M and were in agreement with average plasma concentration ( C av ) of resveratrol reported in previous studies [19]. We did not investigate the compound concentration that reach the maximum plasma level ( C max ) and the area under the curve (AUC) or perform other detailed pharmacokinetic analyses in the present study because the pharmacokinetics of resveratrol have been extensively studied in humans [1921]. As expected, resveratrol was not detected in any of the plasma samples collected at baseline or in the samples derived from the control group (Figure 1(a)).…”
Section: Resultssupporting
confidence: 90%
“…The plasma resveratrol concentrations measured at after two and four weeks of resveratrol administration ranged from 0.7 to 2.55  μ M and were in agreement with average plasma concentration ( C av ) of resveratrol reported in previous studies [19]. We did not investigate the compound concentration that reach the maximum plasma level ( C max ) and the area under the curve (AUC) or perform other detailed pharmacokinetic analyses in the present study because the pharmacokinetics of resveratrol have been extensively studied in humans [1921]. As expected, resveratrol was not detected in any of the plasma samples collected at baseline or in the samples derived from the control group (Figure 1(a)).…”
Section: Resultssupporting
confidence: 90%
“…For the same reason, we do not review the efforts based on formulations or vehiculation by carriers, such as liposomes and nanoparticles (reviewed, e.g., in Ref. ).…”
Section: Strategies To Improve Bioefficacy Of Resveratrolmentioning
confidence: 99%
“…However, even 1 μM concentrations are hard to reach in animals through oral administration of resveratrol, largely because of elaboration by phase II metabolism . Therefore, translation of laboratory results into applications for human health may be problematic . Hence, it would be of great help to increase resveratrol levels, even modestly, and/or to modify its tissue distribution.…”
Section: Introductionmentioning
confidence: 99%
“…RSV has poor water solubility and thus has to be bound to plasma proteins to assure its body distribution and bioavailability [66]. Indeed, in its transport, RSV can bind to serum proteins [67] such as lipoproteins, hemoglobin, and albumin which facilitate its carrier mediated cellular uptake and then it can passively diffuse through the plasma membrane [68,69] investigated the binding properties of RSV to plasma proteins, such as human serum albumin (HSA) and hemoglobin (Hb) and confirmed that both complexes formed are spontaneous and exothermic. The binding constant of RSV-HSA complex is larger than that of RSV-Hb, which indicates the higher affinity of HSA to RSV.…”
Section: Distributionmentioning
confidence: 99%